Incidencia del buen gobierno corporativo sobre el valor de las acciones de las empresas agrarias e industriales listadas en la Bolsa de Valores de Lima - Asmat Vásquez, Pamela Lylibeth (2017)
The present research studies the possible relationship between the application of the Principles of Good Corporate Governance and the value of the shares of agricultural and industrial companies listed on the Lima Stock Exchange between 2014, 2015 and 2016; Taking into account the information presented in the "Report on compliance with Good Corporate Governance", which groups these practices according to the 5 pillars: I) Shareholders 'rights, II) General shareholders' meeting, III) Directors and senior management, VI) Risk And compliance and V) Transparency of information. In this sense, the research was carried out under a descriptive, qualitative, long-term and non-experimental design. We sampled 50 companies listed on the Lima Stock Exchange, 16 in the agricultural sector and 34 in the industrial sector. This sample was calculated using the multi-stage probabilistic method. The analysis consisted in measuring the degree of compliance with good corporate practices and comparing it with the variation that presented the value of its shares, for the years 2014, 2015 and 2016. The result was that there is not enough evidence to show a relationship between the variables, as it was found that companies that increased compliance with the Corporate Governance Principles did not show an increase in the value of their shares; and companies that did not vary in compliance, the value of their shares doubled.